Female Ghosts in Southeast Asian Culture: The Narratives on Body in Pee Mak Phrakanong in Thailand and The Story of The Cotton Tree in Vietnam from the Gender Perspective - Vu Thi Trang (수완나부미, 2025)
Female ghosts are relatively common figures in Southeast Asian folklore. Besides studies on female ghosts from the perspective of spiritual symbols, studies from a gender perspective expose cultural constructions and constraints that produce trauma in individuals. By comparing the Nak ghost in the movie Pee Mak Phrakanong in Thailand and the female ghost in The Story of The Cotton Tree in Vietnam, this article argues that folk authors create the figure of female ghosts to release women’s desires and reveal their sense of social resistance. The openness and boldness in the concept of sexuality, sensuality, and the power of beauty since the medieval period also show the seeds of feminism in Southeast Asia before the reception of Western feminism. In addition, this research contributes to promoting the endogenous strength of indigenous and once-vulnerable areas and communities.